Revolution of digital communication and Asian competitive creativity chasm - Wickramasinghe, C. N.; Ahmad, Nobaya (2009)
This study aims to identify changes that have taken place in the Asian technological creativity after the post-communication revolution of digital technologies. After examining the utility patent applications forwarded to the US Patent Office by 24 Asian countries between 1965 to 2007, the study partially supports the claim that the “digital communication revolution have influenced the competitive creativity development in Asia.” However, the development growth model is shaped like a snail shell, and digital technologies have not been the silver bullet that promoted the leapfrogging of creativity in stagnating countries. Information and communication technologies (ICT) should be considered as a means of technological learning rather than the end of creativity development. The challenge of strengthening stagnating Asian countries to become competitive and innovative nations will continue until the next decade. Unless necessary steps are taken to improve technological learning and local innovations in stagnating countries, their technological dependency will increase and thus deepen the marginalization in the coming eras.